Propuesta de un mapa de procesos para mejorar la competitividad de la empresa Import Titans B&P E.I.R.L. 2015 - Zavaleta Lamela, Ralph Ivan (2017)
ABSTRACT In general the organizations are the economical base of a society because they generate labour, goods, services and satisfy all kinds of needs of a determined society. This enquiry is attempted to contribute with a better competitivity of IMPORT TITANS B&P E.I.R.L. not only at domestic level but also at external one. That is why this research work called “PROPOSALS OF A PROCESS MAPPING TOGET BETTER COMPETITIVITY OF IMPORT TITANS B&P ENTERPRISE 2015” has as a general objective to contribute with a better IMPORT TITANS B&P Entrerprise competitivity. The study design was experimental, descriptive and transversal to abtain results the technique survey, survery and FODA analysis were used. At the same instruments such as questionnaire, interview guide and FODA analysis were also uset. The units -research subjects- were out of 35 stakeholders distributed among managers, cooperators, suppliers and clients of IMPORT TITANS B&P Enterprise. One of the main conclusions is the one related to import TITANS B&P Enterprise does not present a process mapping and consequently is not competitive as shown in the out comes from tables and figures so the refore it is compulsory to propose a process mapping to accomplish a better competitivity.